2022
DOI: 10.1037/xge0001073
|View full text |Cite
|
Sign up to set email alerts
|

Caring is costly: People avoid the cognitive work of compassion.

Abstract: Compassion-the warm, caregiving emotion that emerges from witnessing the suffering of others-has long been considered an important moral emotion for motivating and sustaining prosocial behavior. Some suggest that compassion draws from empathic feelings to motivate prosocial behavior, while others try to disentangle these processes to examine their different functions for human pro-sociality. Many suggest that empathy, which involves sharing in others' experiences, can be biased and exhausting, whereas warm com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 88 publications
(257 reference statements)
1
36
0
Order By: Relevance
“…Another crucial point to note is that while critics of empathy usually recognize that empathy is subject to motivational biases, they fail to make the same judgment for compassion. However, results of a recent study support the view that compassion suffers from some of the same biases as empathy, perhaps even to a greater degree (Scheffer et al, 2021). This study indicated that participants perceived compassion as more cognitively costly than empathy, especially when applied to strangers, which is at odds with the view of compassion as less exhausting than empathy and more likely to lead to sustained helping (Bloom, 2017).…”
Section: Empathy As a Value-based Choicementioning
confidence: 64%
See 2 more Smart Citations
“…Another crucial point to note is that while critics of empathy usually recognize that empathy is subject to motivational biases, they fail to make the same judgment for compassion. However, results of a recent study support the view that compassion suffers from some of the same biases as empathy, perhaps even to a greater degree (Scheffer et al, 2021). This study indicated that participants perceived compassion as more cognitively costly than empathy, especially when applied to strangers, which is at odds with the view of compassion as less exhausting than empathy and more likely to lead to sustained helping (Bloom, 2017).…”
Section: Empathy As a Value-based Choicementioning
confidence: 64%
“…Much of the disagreement surrounding the utility of empathy can be attributed to the nonoverlapping definitions of empathy used in the field. The fuzzy definitions of empathy and compassion have also been pointed out by several different researchers (Neumann et al, 2015;Cuff et al, 2016;Västfjäll et al, 2017;Eklund and Meranius, 2021;Scheffer et al, 2021). Indeed, the lack of a consistent definition of empathy and compassion is a crucial issue which holds back progress in this area of research.…”
Section: Defining Empathymentioning
confidence: 92%
See 1 more Smart Citation
“…C&P interprets these findings as suggesting that the driving mechanism behind compassion collapse is active down-regulation of emotion that only occurs when people themselves expected to help —a finding that supports the motivated emotion regulation account over the affect trigger explanation. While this is only studying one of three studies in the C&P 2011 paper, this particular finding has been cited several times in support of the notion of “empathy/compassion as a choice” ( Zaki, 2014 ; Cameron, 2017 ; Cameron et al, 2019 , 2022 ; Scheffer et al, 2021 ) and is an important contribution for a critical experiment demonstrating a boundary condition for compassion collapse.…”
Section: Introductionmentioning
confidence: 85%
“…(1 = calm; 9 = aroused), and "How negative/positive do you currently feel?" (1 = negative; 9 = positive) using self-assessment manikins (Bradley & Lang, 1994; a similar approach was used to assess state experiences in Scheffer et al, 2021).…”
Section: Cognitive Costs and Blame Choice 33mentioning
confidence: 99%